Pemberdayaan Kelompok Wanita Tani Melalui Pengolahan Limbah Organik Rumah Tangga Menjadi Ekoenzim di Desa Padang Lampe, Pangkep - Hasnaeni Hasnaeni; Nurmaya Effendi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The purpose of this Community Partnership Program activity is to improve the knowledge, attitudes, and skills of the Mappideceng farmer women's group, Padang Lampe Village, Pangkep, in managing household organic waste into eco-enzyme as multipurpose products as a form of their active role in reducing household waste production and minimizing environmental pollution. In achieving this goal, participatory approach methods are used through counseling, interactive discussions, and training to increase partners' knowledge in managing their household organic waste into eco-enzyme products that can be used as active ingredients for cleaning household appliances and fertilizer for home plants, which are certainly environmentally friendly and has economic value. We use pre-post test questionnaires during the activity process to observe and evaluate partner groups' knowledge, attitudes, and skills changes. Our coaching system provides education and training with active participation, discussion, and question and answer. This empowerment program shows that there has been an increase in partners' knowledge, attitudes, and skills in managing household organic waste into eco-enzymes. Furthermore, we hope that the Mappideceng Farmer Women group, Padang Lampe Village, Pangkep, can apply and disseminate their knowledge and skills in managing household organic waste so that it can help reduce environmental pollution and improve their health status.